Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Dalam Kurikulum Merdeka pada Siswa Kelas II di SDN 3 Tanjung Tahun Ajaran 2023/2024 - AGUSTIANI, MERI LUKIANA; Marzoan; Taufik , M. (Lembaga Bale Literasi, 2024)
The aim of this research is to determine the implementation of the project to strengthen the profile of Pancasila students (P5) in the independent curriculum for class II students at SDN 3 Tanjung and to find out the inhibiting factors for the project to strengthen the profile of Pancasila students (P5) for class II students at SDN 3 Tanjung. The population in this study was 30 people, namely class II students at SDN 3 Tanjung. The instruments used in this research were interviews, observation and documentation. The method used is a descriptive qualitative method. The results of this research show that in implementing the project to strengthen the profile of Pancasila students (P5) in class II at SDN 3 Tanjung, there were several obstacles during the implementation of the P5 project, including, 1) Students lacked focus, 2) Lack of teacher understanding about the P5 project , 3) Lack of time to implement P5. Students have been categorized as creative, because students have ideas and discover new things when implementing the project to strengthen the Pancasila student profile (P5).